Neuroprotective effect of Dl-3-n-butylphthalide against ischemia–reperfusion injury is mediated by ferroptosis regulation via the SLC7A11/GSH/GPX4 pathway and the attenuation of blood–brain barrier disruption - Xu, Shuangli; Li, Xuewei; Li, Yutian; Li, Xiangling; Lv, E.; Zhang, Xiaojun; Shi, Youkui; Wang, Yanqiang (Frontiers in Aging Neuroscience, 2023)
Abstract Background: Stroke is one of the most severe diseases worldwide, resulting in physical and mental problems. Dl-3-n-butylphthalide (Dl-NBP), a compound derived from celery seed, has been approved for treating ischemic stroke in China. No study has evaluated how Dl-3-n-butylphthalide affects the ferroptosis SLC7A11/GSH/GPX4 signal pathway and blood-brain barrier (BBB) PDGFRβ/PI3K/Akt signal pathways in the rat middle cerebral artery occlusion/reperfusion (MCAO/R) model of ischemic stroke. Methods: Sprague-Dawley rats were used to develop the MCAO/R model. Our study used three incremental doses (10 mg/kg, 20 mg/kg, and 30 mg/kg) of Dl-3-n-butylphthalide injected intraperitoneally 24 h after MCAO/R surgery. The neuroprotective effect and success of the model were evaluated using the neurofunction score, brain water content determination, and triphenyl-tetrazolium chloride-determined infarction area changes. Pathological changes in the brain tissue and the degree of apoptosis were examined by hematoxylin and eosin, Nissl, and terminal deoxynucleotidyl transferase dUTP nick end labeling staining. In addition, pathway proteins and RNA expression levels were studied to verify the effects of Dl-3-n-butyphthalide on both pathways. At the same time, commercial kits were used to detect glutathione, reactive oxygen species, and malondialdehyde, to detect oxidative stress in brain tissues. Results: The middle dose of Dl-3-n-butylphthalide not only improved MCAO-induced brain dysfunction and alleviated pathological damage, brain inflammatory response, oxidative stress, and apoptosis but also protected against ferroptosis and reduced BBB damage. These changes resulted in improved neurological function in the cerebral cortex. Conclusions: We speculate that Dl-3-n-butylphthalide has a neuroprotective effect on focal cerebral ischemia/reperfusion, which may be mediated through ferroptosis-dependent SLC7A11/GSH/GPX4 signal pathway and PDGFRβ/PI3/Akt signal pathway.